2016
DOI: 10.1136/bmjopen-2015-009345
|View full text |Cite
|
Sign up to set email alerts
|

Sleep among bereaved caregivers of patients admitted to hospice: a 1-year longitudinal pilot study

Abstract: ObjectivesThis pilot study aimed to describe the sleep of partners and other family caregivers prior to and in the first year after a hospice patient's death. The study also evaluated the feasibility of the study protocol and determined the effect sizes in preparation for a full-scale study.DesignThe pilot study used a longitudinal, descriptive and comparative design.Setting and participantsParticipants included primary family caregivers of patients admitted to a hospice in Oslo, Norway.Primary outcomeCaregive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…The Pittsburgh Sleep Quality Index (PSQI) is a screening tool for sleep dysfunction in non‐clinical and clinical samples, and comparisons can be made across populations in terms of global PSQI scores (Buysse, Reynolds III, Monk, Berman, & Kupfer, ; Mollayeva et al, ). Several studies have reported sound reliability and validity for the 19‐item self‐report measure (Mollayeva et al, ), and the scale has been used effectively in studies of caregivers (e.g., Lerdal et al, ). An overall score is generated from 7 subcomponents that assess: sleep duration, sleep latency, habitual sleep efficiency, sleep disturbances, use of sleep medication, daytime dysfunction and subjective sleep quality.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pittsburgh Sleep Quality Index (PSQI) is a screening tool for sleep dysfunction in non‐clinical and clinical samples, and comparisons can be made across populations in terms of global PSQI scores (Buysse, Reynolds III, Monk, Berman, & Kupfer, ; Mollayeva et al, ). Several studies have reported sound reliability and validity for the 19‐item self‐report measure (Mollayeva et al, ), and the scale has been used effectively in studies of caregivers (e.g., Lerdal et al, ). An overall score is generated from 7 subcomponents that assess: sleep duration, sleep latency, habitual sleep efficiency, sleep disturbances, use of sleep medication, daytime dysfunction and subjective sleep quality.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported sound reliability and validity for the 19-item self-report measure (Mollayeva et al, 2016), and the scale has been used effectively in studies of caregivers (e.g., Lerdal et al, 2016). An overall score is generated from 7 subcomponents that assess: sleep duration, sleep latency, habitual sleep efficiency, sleep disturbances, use of sleep medication, daytime dysfunction and subjective sleep quality.…”
Section: Pittsburgh Sleep Quality Indexmentioning
confidence: 99%
“…Sleep problems commonly have a negative impact on the health and well-being of FCs. [9][10][11] Sleep disturbance is used to describe the symptoms of perceived or actual alteration of sleep patterns. 12 The criteria for sleep disturbance include sleeping for less than 7 hours, sleep latency of more than 20 minutes, wake after sleep onset (WASO) of more than 10%, daytime napping of more than 2 hours, and a sleep efficiency of less than 80%.…”
Section: Introductionmentioning
confidence: 99%
“…23 Individuals with sleep disturbance may be at risk of depression, 15,24 anxiety, 21 immune deficiency, 25 cardiovascular disease, 26 and a poor quality of life. 27 Although several studies have investigated the sleep quality of FCs 10,18 and the risk factors for sleep disturbance, 11,15 few studies have followed up FCs until the patients' death to explore the changes in sleep quality throughout the patients' dying process, and no study has comprehensively included the predisposing, precipitating, and perpetuating factors in investigating factors affecting the sleep quality of FCs.…”
Section: Introductionmentioning
confidence: 99%
“…The MCID in a sample of patients with sleep disturbance is -3 (Hughes et al, 2009). With proven reliability and validity (Mollayeva et al, 2016), the PSQI has been used effectively in longitudinal studies of caregiver outcomes (Lerdal et al, 2016).…”
Section: Measures Administered To Family Membersmentioning
confidence: 99%